Some Considerations of Restorative Justice Before and Outside of Contemporary Western States - Kuhlmann, Annette; Kury, Helmut (Kriminologijos studijos, 2018)
[full article, abstract in English; only abstract in Lithuanian] This article provides an overview of the main themes and controversies in the restorative justice discussions in Europe and the US with special attention to the role of victims and mediators. This discussion is contextualized through a short description of the history of both state-centered and community-oriented restorative systems in response to law violation. Indigenous and pre-state formation responses to crime have predominantly been of a restorative nature with an interest in healing the harm experienced by all participants, aimed at addressing social problems and strengthening the community as a whole.